ANALISIS PENGARUH INFLASI DAN PERTUMBUHAN EKONOMI TERHADAP PENGANGGURAN TERBUKA DI KABUPATEN LOMBOK TENGAH TAHUN 2016-2021 - Nurul Aida Susanti; Rosita, Rosita; Ahmad Suhendri; Mukti Ardiansyah, Akhdiyat; Novia Irianti, Nana (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2024)
This study is entitled "ANALYSIS OF THE EFFECT OF INFLATION AND ECONOMIC GROWTH ON OPEN UNEMPLOYMENT IN CENTRAL LOMBOK REGENCY IN 2016-2021". In this study, the researcher wants to see how inflation and economic growth affect open unemployment in Central Lombok Regency in 2016-2021. The type of this research is Quantitative research with an associative approach. The analytical tool used in this study is multiple linear regression analysis. The results of this study are that the R-square value is 0.664 with a significance value (α) or alpha of 0.05 (5%). The R-square value in this study has a meaning, namely the influence of the inflation and economic growth variables is able to explain the unemployment variable in Central Lombok Regency by 0.664 one-unit or 66.4%, and this figure shows a large influence and meets the regression criteria. While the rest is influenced by other variables not included in this study by 0.336 or 3.36%. Partially, the influence of the inflation and economic growth variables is not significant in influencing unemployment in Central Lombok Regency from 2016-2021. Simultaneously, the inflation and economic growth variables are not significant in influencing unemployment in Central Lombok Regency from 2016-2021. Meanwhile, the dominant variable influencing unemployment in Central Lombok Regency is the economic growth variable.